2017
DOI: 10.1530/joe-17-0039
|View full text |Cite
|
Sign up to set email alerts
|

Akt signaling as a mediator of cardiac adaptation to low birth weight

Abstract: Intrauterine insults, such as poor nutrition and placental insufficiency, can alter cardiomyocyte development, and this can have significant long-term implications for heart health. Consequently, epidemiological studies have shown that low-birth-weight babies have an increased risk of death from cardiovascular disease in adult life. In addition, intrauterine growth restriction can result in increased left ventricular hypertrophy, which is the strongest predictor for poor health outcomes in cardiac patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 148 publications
(150 reference statements)
1
16
1
Order By: Relevance
“…Interestingly, we found that maternal RSV supplementation increased the mRNA expression of IGF1 and decreased the expression of IGF2R. These signalling molecules are involved in physiological and pathological cardiac growth, respectively Wang et al 2012aWang et al , 2017. Although IGF1 mRNA expression was increased in the RSV-treated group, there was no evidence that downstream AKT/mTOR signalling was increased.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Interestingly, we found that maternal RSV supplementation increased the mRNA expression of IGF1 and decreased the expression of IGF2R. These signalling molecules are involved in physiological and pathological cardiac growth, respectively Wang et al 2012aWang et al , 2017. Although IGF1 mRNA expression was increased in the RSV-treated group, there was no evidence that downstream AKT/mTOR signalling was increased.…”
Section: Discussionmentioning
confidence: 72%
“…; Wang et al . , ). Although IGF1 mRNA expression was increased in the RSV‐treated group, there was no evidence that downstream AKT/mTOR signalling was increased.…”
Section: Discussionmentioning
confidence: 99%
“…miR-18a is a member of the miR-17-92 family cluster, which includes 6 individual miRNAs: miR-17, miR-18a, miR-19a, miR-20a, miR-19b1 and miR-92a1, which are amplified in lymphomas and other cancer cells (13)(14)(15). This cluster and its paralogues play important roles in cancer development due to their ability to suppress the expression of a number of tumor-associated proteins, such as p53 and Akt (13)(14)(15), the overexpression of which promotes cell viability and reduces apoptosis by regulating cell cycle progression (16)(17)(18)(19). The miR-17-92 cluster also plays an important role in normal growth and skeletal development.…”
Section: Microrna-18a Inhibits Cell Growth and Induces Apoptosis In Omentioning
confidence: 99%
“…IUGR lambs of pregnancies with placental restriction have increased cardiac phosphorylation of the insulin receptor, increased glucose transporter-1 (GLUT-1), and increased pyruvate dehydrogenase kinase-4 compared with controls at 21 days of age (81,82), which suggests greater glycolysis. Interestingly, this altered metabolism is coupled with greater left ventricle (LV) weight relative to body weight (LV hypertrophy; LVH) compared with controls (83).…”
Section: Introductionmentioning
confidence: 99%